POLICE OF THE REPUBLIC OF POLAND: REGULATORY AND ORGANIZATIONAL ASPECTS (Law and Safety, 2018)
The normative regulation and specifics of the organization of police forces of Poland have been researched; the Law on the Police of 1990 and other normative acts in this area have been analyzed.It has been noted that after the democratic revolution of 1988-1989, the reform of the Polish police forces has become one of the priorities of democratic government. The system of agencies of the Ministry of Interior has already undergone changes at an early stage of reforms, when in April 1990 the Laws on the Ministry of Interior, on the Police and the Office of State Protection have been adopted. Instead of the militia, they created the police, and the vast majority of former officers of militia, except a part of the leadership, automatically became police officers.It has been demonstrated that the central agency of state administration responsible for protecting people’s safety and maintaining public safety and law and order is the Chief Commandant of the Police, who is subordinated to to the Minister responsible for internal affairs. The Chief Commandant of the Police is the head of all police officers. The Commandant of the Police is appointed and withdrawn by the Chairman of the Council of Ministers on the recommendation of the Minister responsible for internal affairs.Attention has been paid to the special powers of the police. In the case of disobedience to the police ordinance issued according to the law, police officers may use the following means of immediate coercion: 1) physical, technical and chemical means for deprivation of freedom of movement or convoy of persons, as well as for stopping trains; 2) official batons; 3) water stopping devices; 4) official dogs and horses; 5) non-penetrating bullets shot with firearms. Police officers may use only such coercive measures as are appropriate to the needs arising from the present situation and are necessary to achieve subordination to the issued ordinance.It has been concluded that the process of reforming the Police of the Republic of Poland was long, occurred in several stages for almost three decades, its main factor was the commitment to implement the standards and values of the European Union’s police activities, the joining of which was a strategic goal of the state. Besides, nowadays the organization of the Police in Poland confirms the balance between organizational efforts and resource provision, which are focused on achieving clear results in efficiency indicators of the police forces.
Keywords: Poland, police, human rights, European Union.